KANDUNGAN ANTIOKSIDAN ALGA MERAH EUCHEUMA COTTONII DENGAN METODE PENGERINGAN YANG BERBEDA - Amelia, Resky; Tanod, Wendy Alexander (KAUDERNI : Journal of Fisheries, Marine and Aquatic Science, 2016)
The antioxidant compound is one compound that is much sought after by researchers. Antioxidant compounds could counteract free radicals easily react with molecules such as proteins, fats, carbohydrates, and DNA. Red algae Eucheuma cottonii containing bioactive potential as natural antioxidants. Drying algae by farmers generally utilize solar energy. Drying in this way can damage the content of antioxidant compounds. This study aims to assess the proper drying method in order to minimize damage to the E. cottonii antioxidant compounds. This research was using four different drying methods of treatment and 3 replicates, in the determination of IC50 values. The yield showed dried by the sun of 70.9%, dried at room temperature with the aid of a fan at 83.3%, is dried using an oven with atemperature of 70-800C for 87.8% and dried using an oven with a temperature of 50- 600C by 73%. IC50 values in the dried by the sun at 693.90 ppm, dried at room temperature with the aid of a fan at 593.19 ppm, dried using an oven with a temperature of 70-800C at 232.87 ppm and dried in an oven at a temperature of 50-600C 419.76 ppm. Levels of antioxidants found in E. cottonii either dried using an oven or dried by the sun and the temperature of the room, including the antioxidant weak.